POTENSI BAKTERI KITINOLITIK NR09 PADA BEBERAPA MEDIA PEMBAWA DALAM MENGHAMBAT PERTUMBUHAN JAMUR PATOGEN Sclerotium rolfsii dan Fusarium oxysporum PADA BENIH CABAI MERAH (Capsicum annuum L.) - Deswidya Sukrisna Hutauruk (Universitas Medan Area, 2018)
This study was aims to determine the viability of chitinolytic bacterial isolates in some carrier media and to know the potential of chitinolytic bacterial isolates in various carrier media in controlling the disease of sprout caused by F. oxysporum and S. rolfsii on red pepper plant. The method used by measuring the viability and ability of bacteria in growing media and carrier media on MGMK media after storage of carrier media for 90 days. Bacteria NR09 has good viability on peat carrier media and palm oil bunch compost and has the potential to inhibit attack of pathogenic fungi S. rolfsii and F. oxysporum.